THE SOCIAL SIGNIFICANCE OF GENDER ROLES AND DISTRIBUTION OF RESPONSIBILITIES IN THE FAMILY INSTITUTE - Khabibjonova Nodira Shavkat kizi (Bright Mind Publishing, 2026)
The article scientifically and theoretically illuminates the essence of the family institution as a social system and its role in the development of society. The formation, structure, and mechanisms of stable functioning of the family as a social institution are analyzed. It also reveals the significance in society of the main institutional functions of the family - reproductive, educational, economic, socializing, spiritual-educational, and social control functions. Special attention will be paid to the transformation processes taking place in the institution of the family in the context of modern social changes and their impact on the stability of the social system.
Keywords: Family institution, institutional functions, reproductive function, educational function, socialization, economic function, spiritual values, social control.